Acclimation History of Elevated Temperature Reduces the Tolerance of Coralline Algae to Additional Acute Thermal Stress - Page, Tessa M.; Bergstrom, Ellie; Diaz-Pulido, Guillermo (Frontiers in Marine Science, 2021)
Increasing atmospheric CO2 is driving major environmental changes in the ocean, such as an increase in average ocean temperature, a decrease in average ocean pH (ocean acidification or OA), and an increase in the number and severity of extreme climatic events (e.g., anomalous temperature events and heatwaves). Uncertainty exists in the capacity for species to withstand these stressors occurring concomitantly. Here, we tested whether an acclimation history of ocean warming (OW) and OA affects the physiological responses of an abundant, reef-building species of crustose coralline algae (CCA), Porolithon cf. onkodes, to chronic and acute thermal stress. To address this, we exposed algae to varying temperature and pH levels for 6 weeks and this chronic treatment experiment was followed by an acute exposure to an anomalous temperature event (+4–6°C from acclimation temperature). Net photosynthetic rate was negatively affected across all treatments by increasing temperature during the acute temperature event, however, algae acclimated to the control temperature were able to maintain photosynthetic rates for +4°C above their acclimation temperature, whereas algae acclimated to elevated temperature were not. Average relative change in O2 produced resulted in a 100–175% decrease, with the largest decrease found in algae acclimated to the combined treatment of elevated temperature and reduced pH. We conclude that acclimation to chronic global change stressors (i.e., OW and OA) will reduce the tolerance of P. cf. onkodes to anomalous increases in temperature, and this may have implications for reef building processes.